The Implementation of the Peaceful End of Life Theory in Breast Cancer Patient - Antonia Hamu; Maria Syelvrida Tumina; Febtian Cendradevi Nugroho; Maria Agustina Making; Roswita Victoria Rambu Roku; Luisa Bethelin Titi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cancer is a major global health concern and a leading cause of mortality among non-communicable diseases. It involves the uncontrolled growth of abnormal cells that are malignant, invasive, and capable of metastasizing to distant organs. Among the various types of cancer, breast cancer is one of the most prevalent and is often detected at a late stage. The peaceful end of life theory provides comfort, dignity and emotional support to the patient. This study aims to analyze the implementation of the Peaceful end of life theory in Breast Cancer patients through nursing process approach. The method used is case study. In the nursing assessment, the patient reported experiencing pain, anxiety, and worry about their deteriorating condition. They expressed feelings of meaninglessness and helplessness, and showed reluctance to meet others due to fear of being ridiculed. Based on the Standardized Nursing Diagnosis (SDKI), the nursing diagnoses included chronic pain related to tumor infiltration, anxiety related to the threat of death, spiritual distress related to end-of-life concerns, nutritional deficit related to increased metabolic needs, self-care deficit, and impaired body tissue integrity. The nursing interventions aimed to improve the patient’s quality of life, promote a peaceful end of life, provide emotional support, facilitate intimacy with family, alleviate pain, and offer empathy to both the patient and their family. The implementation of the Peaceful end of life Theory involves not only the patient but also the active involvement of the family, as it enhances the quality of life by providing support and aiding in decision-making.